Relation between photoluminescence emission and local order-disorder in the CaTiO3 lattice modifier - de Lazaro, Sergio; Milanez, Juliana; de Figueiredo, Alberthmeiry T.; Longo, Valeria M.; Mastelaro, Valmor R.; De Vicente, Fabio S.; Hernandes, Antonio C.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (American Institute of Physics (AIP), 2007)
In this letter, the authors propose that photoluminescence emission in CaTiO3 is affected not only by disorder in the lattice former but also by structural disorder in the lattice modifier. Structural disorder was evaluated by Ti, Ca K-edge x-ray absorption near-edge structure experiments and by photoluminescence emission. The preedge feature of the Ca K edge was related to the intensity of photoluminescence emission. The results of the preedge feature of the Ca K-edge x-ray absorption near-edge structure confirm the presence of different Ca coordination numbers, namely, Ca-O-11 and Ca-O-12. (c) 2007 American Institute of Physics.